Succinic Acid Production from Monosaccharides and Woody and Herbaceous Plant Hydrolysates Using Metabolically Engineered Corynebacterium glutamicum§ - Dae-Seok Lee; Eun Jin Cho; Seryung Kim; Dien Thanh Nguyen; Hyeun-Jong Bae (Food Technology and Biotechnology)
Research background. Succinic acid from lignocellulosic biomass is a sustainable alternative for biochemical production that is an environmentally friendly substitute for petroleum-based chemicals. The aim of this study is to evaluate the effects of variations in hemicellulose content and cellulose fibre structure within the microfibrils of woody and herbaceous plants on the enzymatic saccharification and succinic acid production efficiency of Psod:SucE12-ΔldhA, a strain overexpressing the succinic acid transporter (SucE). Experimental approach. The study investigated the influence of different monosaccharide combinations on succinic acid production, focusing on combinations with mannose compared to glucose alone. Additionally, hydrolysates from different lignocellulosic biomass — bamboo, oak, poplar, pine and spent coffee grounds — were analysed to determine the most favourable bioresource for succinic acid production. Results and conclusions. Monosaccharide combinations containing mannose resulted in 2.20-2.48 times higher succinic acid production than glucose alone, indicating a positive influence of mannose on succinic acid metabolism. Among the lignocellulosic biomass hydrolysates, bamboo, with its higher xylose content than woody plants, was the most efficient bioresource for succinic acid production (23.38–24.12 g/L within 24 h), followed by oak, poplar, pine and spent coffee grounds. Therefore, improving the xylose consumption rate is crucial for increasing succinic acid production from lignocellulosic biomass and increasing market competitiveness. Novelty and scientific contribution. This research emphasises the potential of lignocellulosic biomass, especially bamboo, as a sustainable feedstock for succinic acid production. The novelty of the study lies in the detailed investigation of how hemicellulose content and cellulose fibre structure affect enzymatic saccharification and fermentation. The significant influence of mannose and xylose on the succinic acid yield provides key insights for the optimisation of biomass use in biochemical production. These findings promote bio-based chemical production, reduce reliance on fossil fuels and improve industrial sustainability.